Characteristics of thermophilic granulation processes in UASB reactors. (26th February 2010) - Zhou, Weili; Imai, Tsuyoshi; Ukita, Masao
Thermophilic granulation processes were examined with synthetic wastewaters and were compared with the parallel mesophilic ones. The results indicated that granules could be formed well under compatible thermophilic surroundings in both carbohydrate- and protein-rich substrates. Compared with the mesophilic process, thermophilic granulation took relatively longer time, but thermophilic UASB reactors had much higher treatment capacity and efficiency than the mesophilic ones. Under the same running conditions, thermophilic sludge had lower contents of Extracellular Polymer (ECP) than mesophilic ones, which might be one of the reasons of the longer period needed for thermophilic granulation.